Hubungan antara Attachment Orangtua-Anak dan Hubungan Antarsaudara Kandung pada Remaja Awal - Annisa Khairani; Rini Hildayani (Jurnal Ilmiah Psikologi MIND SET, 2012)
The purpose of this research is to examine the relationship between attachment qualities and sibling relationship in early teens. Sibling relationship consists of four dimensions warmth, conflict, rivalry, and relative power. This study uses 97 individuals aged 11 to 14 which have siblings with an age difference less than 5 years. Attachment quality is measured by using Security Scale. Sibling relationship is measured by using Sibling Relationship Questionnaire. Results of this study show that there are significant correlation between attachment quality and sibling relationship in three dimensions warmth, conflict, and rivalry. There are no significant differences in relative power dimensions. Additional analysis results also found that family constellation (age differences, relative age, gender difference between siblings) are also related to several dimensions of sibling's relationship. Researcher also found significant correlation between mother's work hours with attachment quality.